Evaluation of regional government policies in handling post-earthquake disaster - Rahim, Abdur; Andriansyah; Satispi, Evi; Hermansyah, Andi; Muksin, Zainal (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
Disasters have had a huge impact both physically, psychologically and socially, the magnitude of the impact caused by these disasters means it is necessary to develop communities that have the ability to organize, learn and adapt in facing disasters. The aim of this research is to identify and describe the evaluation of the impact and behavior of the community on economic conditions after the earthquake disaster and to find out the local government's public policy in handling this case. Using qualitative methods with a case study approach, literature study, and secondary data processing from various social elements. Apart from that, data collection was carried out by interviewing sources who felt the direct impact of the earthquake disaster. The research results show that the impact of the post-earthquake disaster felt by the community is generally in the "severe" classification. The socio-economic conditions of the community cover several aspects, starting from geographical conditions that are in disaster-prone zones, health conditions are very worrying after the disaster. The conclusions of this research show that the consequences of the earthquake disaster are considered quite large, which has an impact on the regional economy. Damage to infrastructure combined with a backlog of logistics in supply warehouses means that goods that should be distributed cannot be carried out properly.